FYR Macedonia : Agriculture Sector Review - Jaisaard, Rapeepun; Christensen, Garry; Smith, Garry; Gue, David; Nacev, Aleksandar (Washington, DC, 2013)
Economic progress in Macedonia has been variable and slow during the last 10 years. This slow progress is attributable to the succession of political and economic shocks, and the failure to complete economic reform. Agriculture is an important sector in the Macedonia economy, with production and processing contributing around 18% of GDP. As a small economy with a structural deficit in most food commodities, agricultural trade is essential for Macedonia. Current agricultural trade policy, however, constrains agricultural trade. Most Macedonian imports are covered by free trade agreements under the Stabilization and Association Agreement and with regional trading partners. Direct support for agriculture derives from the budget of the Ministry of Agriculture, Forestry and Water Economy, and the activities of the State Office for Commodity Reserves (SOCR). Budget support is minimal due to the severe current fiscal restrictions. Most support comes from SOCR, through its purchases of wheat and tobacco to maintain official floor prices. Macedonia has 1.28 million ha of agricultural land, about half cultivable and half pastures. All socially owned land was nationalized in 1993. Existing irrigation schemes have been reduced from 40% to 13%. The state of the country's irrigation system is poor and crop damage during the variable summer dry period is prevalent. Produce quality suffers from lack of needed infrastructure supporting post-harvest treatment and packing. The priority areas for agriculture, the expansion of production, and increase in productivity, require that resources be available to efficient private producers, including efficient small ones, and a processing and marketing chain, so that they can expand in areas where they are competitive. This will require a comprehensive restructuring of government policies and support.